Faktor-faktor yang Mempengaruhi Profitabilitas Bank Syariah Indonesia dan Malaysia - Ike Dwi Astuti; Nur Kabib (Jurnal Ilmiah Ekonomi Islam, 2021)
One of the benchmarks for state progress in banking which affects economic activity (Khasanah, 2016) . This study aims to determine the factors that influence profitability included CAR, BOPO, FDR, on ROA with NPF as a moderating variable for Indonesian and Malaysian Islamic banking listed in the Financial Services Authority (OJK) and Bank Negara Malaysia (BNM) for the 2014-2019 period. This type of quantitative research with secondary data is in the form of panel data. The sample includes 11 Indonesian Islamic banks and 7 Malaysian Islamic banks. The collection method is to access the annual report on the bank's website. Multiple Linear Regression analysis tool with the Eviews 10 Version application. The analysis used the Descriptive Statistical Test, Stationarity Test, and Multiple Linear Regression Test. The test results include: 1) CAR is not significant to ROA; 2) BOPO is not significant to ROA; 3) FDR is not significant to ROA; 4) CAR with NPF as a moderating variable has a positive and significant effect on ROA; 5) BOPO with NPF as a moderating variable has a negative and significant effect on ROA; 6) FDR with NPF as a moderating variable has a negative and significant effect on ROA.